Analisis Pengaruh Pengumuman Merger Bank Syariah Bumn Terhadap Saham Perbankan Di Indonesia - Rama Wijaya, Andika; Sucia Sukmaningrum, Puji (Fakultas Ekonomi dan Bisnis Islam, 2021)
This study aims to determine the market's reaction to the announcement of the merger of three state-owned Islamic banks against Islamic banking and conventional banking stocks as measured by abnormal returns and trading volume activity. The method used in this study uses an event study with quantitative proximity. To see the abnormal returns, use a market model with an estimated period of 60 days and an event period of 10 days before and 10 days after the announcement of the merger of three state-owned Islamic banks. To determine the sample, purposive sampling was used and 17 stock samples were obtained consisting of 3 samples of sharia stocks and 14 samples of conventional stocks. The analysis technique used in this study used a one-sample t-test and a paired sample t-test if the data were distributed normally. If there is data that is not normally distributed, the analysis technique used is the one sample wilcoxon signed r test .